Sustainability of integrated hypertension and diabetes with HIV care for people living with HIV at primary health care in South Ethiopia: implication for integration - Abebe Sorsa Badacho; Ozayr Haroon Mahomed (BMC Primary Care, 2023)
Abstract Background People living with human immunodeficiency virus (PLWH) have an increased risk of developing noncommunicable diseases (NCDs) compared with people without HIV. The multimorbidity of NCDs and HIV increases the need for integrated care. However, there is a paucity of evidence on the implementation of integrated sustained hypertension and diabetes with HIV care to address the multiple chronic care needs of PLWH in Ethiopia. Objective This study aimed to determine the sustainability of integrated hypertension and diabetes within HIV care for PLWH in primary healthcare (PHC) in southern Ethiopia. Methods The National Health Service Institute for Innovation and Improvement Sustainability Model (NHS- SM) self-assessment tool was used to assess sustainability. HIV care and NCD team members from five PHC facilities in South Ethiopia were included. Participants completed the self-administered NHS-SM assessment tool independently. Result The overall mean sustainability was 43.74 (95% CI: 42.15–45.33). All facilities had an overall sustainability score of less than 55. The perceived benefit beyond helping the patient, the likelihood of adaptability, and perceived alignment with the organizational goal were identified as potential factors promoting sustainability. The perceived lack of an effective system to monitor progress, staff behavior, inadequate staff involvement and training, inadequate senior leadership support and clinical leadership engagement, and infrastructure limitations could negatively affect sustainability. Conclusions Integrating hypertension and diabetes with HIV care sustainably at PHC requires staff involvement and training, staff behavior change communication, ensuring PHC management and clinical leadership (doctors and senior clinicians) engagement, and addressing infrastructure limitations.